Building Loyalty in Consumer Markets - Selivanova, Olga (2010)
In the first chapter this thesis summarizes all different viewpoints of marketers and other experts in business concerning customer loyalty definition. The second chapter discusses a role customer loyalty plays in business of companies. By selecting appropriate definition of customer loyalty, the purpose of this thesis would be to describe all benefits associated with customer loyalty and suggest solution for their expression in economic terms. These topics are discussed in Chapter 3 and 4. In addition in Chapter 5 and Chapter 6 management of customer loyalty and its determinants will be introduced. By selecting those determinants, which are hidden behind customer motivations to purchase company's products or services, and by managing them, company is able to build customer loyalty and enjoy all associated benefits in a form of increased profitability of its business. Finally in the last chapter loyalty programs and their management are discussed, because they are often used as tools to encourage customer loyalty. All these findings are demonstrated in a case study of Palac Flora, a shopping mall in Prague, which introduced its loyalty program a couple of years ago. The final part of this thesis is devoted to conclusion and bibliography.